Ultraconservative, Fertility Sparing Treatment of Bilateral Borderline Ovarian Tumors: A Case Report of a 26-Year-Old, 0-Gravida with an Endometrioid Borderline Ovarian Tumor of the Right Ovary and a Sero-Mucinous Borderline Ovarian Tumor of the Left Ovary and a Review of the Literature - Verta S; Kipp B (Dove Medical Press, 2020)
Stephanie Verta, Barbara Kipp Department of Obstetrics and Gynecology, Lucerne Cantonal Hospital, Lucerne, SwitzerlandCorrespondence: Stephanie Verta Email stephanie.verta@luks.chAbstract: Endometrioid borderline ovarian tumors are rare, entailing a lack of data on their natural history as well as the safety of conservative and ultraconservative surgical management, especially in cases with bilateral borderline ovarian tumors including one of endometrioid differentiation. Therefore, we present such a case and provide a review of the literature on endometrioid borderline ovarian tumors. We report the case of a 26-year-old, 0-gravida with an endometrioid borderline ovarian tumor of the right and a sero-mucinous borderline ovarian tumor of the left ovary treated by fertility sparing, ultraconservative surgery with bilateral cystectomy, completed by staging procedures including omentectomy and peritoneal sampling, as well as endometrial sampling by means of curettage. Reviewing the literature and taking into account the course of our case, we propose the feasibility of an ultraconservative management, including endometrial sampling, in young patients with bilateral borderline ovarian tumors including one of endometrioid differentiation who desire to preserve fertility, followed by a closely monitored follow-up.Keywords: endometrioid borderline ovarian tumor, bilateral borderline ovarian tumor, ultraconservative treatment, fertility sparing surgery, bilateral cystectomy